Economic criteria for the selection of wall formwork - Biruk, Sławomir; Jaśkowski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Planning formwork (selecting systems, designing layout of formwork members) affects the economy of in situ concrete structures. Formwork rental cost, and labor cost of formwork installation and removal, have a significant share in total cost. The paper investigates into the problem of minimizing wall shuttering cost. A mathematical model of the problem of panel layout is proposed, and its operation is illustrated by the case with two optimization criteria.